5PSQ-036 Polypharmacy and deprescribing in HIV-infected elderly population. (March 2019) - Gallardo, S; Pardo, J; March, P; Garreta, G; Sangrador, C; Nicolás, J
Abstract : Background: Human immunodeficiency virus (HIV)-infected elderly population (IEP) must become a deprescribing critical group due to premature aging and high risk of age-related comorbidities and drug interactions. Purpose: To measure the prevalence of polypharmacy in HIV-IEP with antiretroviral therapy (ART). To analyse the need to introduce a deprescribing procedure in pharmaceutical care. Material and methods: An observational, descriptive, transversal study was carried out in April 2018 in a 2 60 000 healthcare area hospital. All HIV-IEP (over 50 years) with active ART were included. Polypharmacy grades were defined as low (concomitant use of 6–10 medications), medium (11–20) and high (over 21), ART included. Recorded variables: demographics (sex, age) and pharmacological (number of concomitant prescribed drugs (ART included) and polypharmacy grade). Data were obtained through electronic prescribing, medical records and the Landtools outpatient drug dispensation database. A review of inappropiate chronic drugs in polymedicated VIH-IEP was carried out in order to prevent risk of falls, fractures, confusion, dementia, hospitalisation and mortality. Drugs included: anticholinergics, long-term antidiabetic agents (sulfonylureas), first-generation antihistamines, antipsychotics, bisphosphonates, cholinesterase inhibitors (CI), nonsteroidal antiinflammatory drugs (NSAIDs), opioids (oxycodone), proton pump inhibitors (PPIs), sedative-hipnotics, selective serotonin reuptake inhibitors (SSRIs) and tricyclic antidepressants (TA). A descriptive statistical analysis was carried out with mean and standard deviation for quantitative variables including absolute and relative frequencies, via SPSS v.24 software. Results: Two-hundred and thirty-seven patients were included, 19.0% presented polypharmacy. Polymedicated patients were 66.6% males, median age 57 years (50–81). The concomitant prescribed medication average was 8.4±2.5: 80.0% presented low-grade polypharmacy, 20.0% medium-grade and zero high-grade. Inappropiate chronic drugs were found in 77.8% of the polymedicated group. Frequency distribution: 42.2% SSRIs, 37.8% PPIs, 22.2% sedative-hipnotics, 17.8% anticholinergics, 15.6% NSAIDs, 13.3% TA, 6.7% sulfonylureas, 6.7% antipsychotics and 2.2% oxycodone. No antihistamines, CI or bisphosphonates treatments. Conclusion: Despite the high rate of polypharmacy, it is lower than results observed in other studies (POINT study). 1 Our population shows a low-grade polypharmacy and a high incidence of inappropiate chronic drugs. Results prove the necessity to implement a deprescribing procedure in this group of patients. References and/or acknowledgements: 1. Morillo Verdugo R, et al. POINT study. Spanish Association of Hospital Pharmacists 62 Congress. Madrid2017. No conflict of interest.